DOI: 10.7146/aul.288.202
|View full text |Cite
|
Sign up to set email alerts
|

Lidar-based Obstacle Detection and Recognition for Autonomous Agricultural Vehicles

Abstract: This thesis would not have been possible without support from a great number of people. First, I would like to thank my main supervisor Rasmus Nyholm Jørgensen for offering me the PhD position and for always seeing (financial) possibilities instead of limitations. You have always defended our interests and helped out during planning and execution of difficult field trials. Thanks to my co-supervisor Henrik Karstoft. You have always been available for technical guidance, discussions, and constructive feedback, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Point cloud classification deals with the issue of discriminating 3D point structures based on their shapes and neighborhoods for various applications, such as vehicle identification and tracking [23], pedestrian-vehicle near-miss detection [24], and background filtering [25]. Kragh [26] proposed two methods for point classification of LiDAR-acquired 3D point clouds, which address sparsity and local point neighborhoods and were used for consistent feature extraction across entire point clouds. One method, based on a traditional processing pipeline, outperformed a generic 3D feature descriptor designed for dense point clouds.…”
Section: Lidar Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Point cloud classification deals with the issue of discriminating 3D point structures based on their shapes and neighborhoods for various applications, such as vehicle identification and tracking [23], pedestrian-vehicle near-miss detection [24], and background filtering [25]. Kragh [26] proposed two methods for point classification of LiDAR-acquired 3D point clouds, which address sparsity and local point neighborhoods and were used for consistent feature extraction across entire point clouds. One method, based on a traditional processing pipeline, outperformed a generic 3D feature descriptor designed for dense point clouds.…”
Section: Lidar Sensorsmentioning
confidence: 99%
“…Together, the two methods showed that sparsity in LiDAR-acquired point clouds can be addressed intelligently by utilizing the known sample patterns. A combination of multiple representations may therefore accumulate the benefits and potentially provide increased accuracy and robustness [26]. To effectively use LiDAR for sensing obstacles in vegetation, LiDAR can be used in combination with stereo cameras to analyze the cloud data points with 2D images.…”
Section: Lidar Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This ensures high resolution at short distance and prevents noisy features at far distance. We use the method from Kragh, Jørgensen and Pedersen () which in Kragh () has shown to outperform the generalized 3D feature descriptor fast point feature histograms (FPFH) (Rusu, Blodow, & Beetz, ) for sparse, lidar‐acquired point clouds. The method scales the neighborhood size linearly with the sensor distance.…”
Section: Approachmentioning
confidence: 99%